On the nilpotency of some modules over group rings - Kurdachenko, L.; Pypka, O.; Subbotin, I. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 512.553We study $RG$-modules that do not contain nonzero $G$-perfect factors. In particular, it is shown that if a group $G$ is finite and $R$ is a Dedekind domain with some additional restrictions, then these $RG$-modules are $G$-nilpotent.